Fiscal federalism and decentralization in India - Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
This paper surveys the state of fiscal federalism in India, in the broader context of decentralization. We begin with an overview of the basic features and recent developments in intergovernmental fiscal relations, including the role of political institutions, the specifics of legislative and budgetary autonomy, assignments of expenditure responsibility and revenue authority, revenue collection mechanisms, the system of intergovernmental transfers, and institutions and mechanisms for borrowing by subnational units. We then provide a diagnosis of accountability mechanisms, examining their quality of functioning and distortions and constraints. In particular, we analyze to what extent, and through what mechanisms, lower-level governments are held accountable to higher-level governments, the extent to which policies of subnational governments are affected by the competition for mobile firms, taxpayers, and investment capital, the functioning of credit markets, including the responsiveness of subnational governments to credit ratings and bond yields, and the role of democratic electoral channels at national and subnational levels in providing accountability in the provision of subnational public goods. Next, we review the implications of the intergovernmental system and accountability mechanisms on the cooperation of subnational governments and the quality of service delivery. We examine the resources and capacity of the subnational entities that areresponsible for key services such as water, sanitation, education and health care, and the impacts of decentralization on service quality and the distribution of benefits among elected officials, citizens and interest groups. Finally, we offer a concluding assessment with suggestions for reform priorities.
Keywords: P26; P35; H1; H7; 330; federalism; decentralization; intergovernmental relations; economic reform; accountability; service delivery; Finanzföderalismus; Dezentralisierung; Wirtschaftsreform; Indien